(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To determine the adherence rate to hemodialysis treatment among chronic kidney disease patients and associated factors at the Nephrology - Hemodialysis Department, Military Hospital 175 in 2024. Methods: A cross-sectional descriptive study was conducted on 264 patients undergoing hemodialysis treatment at the Nephrology - Hemodialysis Department, Military Hospital 175. The study utilized a pre-designed, self-administered questionnaire for chronic kidney disease patients on hemodialysis. Results: The adherence rate to hemodialysis treatment among the study subjects was recorded at 90.91%. A significant association was found between adherence to hemodialysis treatment and the mode of transportation used by chronic kidney disease patients undergoing hemodialysis at the Nephrology - Hemodialysis Department, Military Hospital 175 in 2024. Conclusion: In-depth studies on factors such as quality of care, disease knowledge, psychosocial support, and specific barriers within the healthcare system should be conducted to develop appropriate interventions tailored to the specific context, aimed at improving the quality of care and treatment for chronic kidney disease patients.